Management consensus guidance for the use of rivaroxaban – an oral, direct factor Xa inhibitor - Turpie, Alexander G. G.; Kreutz, Reinhold; Llau, Juan; Norrving, Bo; Haas, Sylvia (Thrombosis and Haemostasis, 2012)
A number of novel oral anticoagulants that directly target factor Xa or thrombin have been developed in recent years. Rivaroxaban and apixaban (direct factor Xa inhibitors) and dabigatran etexilate (a direct thrombin inhibitor) have shown considerable promise in large-scale, randomised clinical studies for the management of thromboembolic disorders, and have been approved for clinical use in specific indications. Rivaroxaban is licensed for the prevention of venous thromboembolism in patients undergoing elective hip or knee replacement surgery, the treatment of deep-vein thrombosis and prevention of recurrent venous thromboembolism, and for stroke prevention in patients with non-valvular atrial fibrillation. Based on the clinical trial data for rivaroxaban, feedback on its use in clinical practice and the authors’ experience with the use of rivaroxaban, practical guidance for the use of rivaroxaban in special patient populations and specific clinical situations is provided. Although most recommendations are in line with the European summary of product characteristics for the approved indications, additional and, in several areas, different recommendations are given based on review of the literature and the authors’ clinical experience.
Keywords: Anticoagulant; practical management; recommendations; rivaroxaban